Innovative solutions for in-situ Cal/Val of satellite altimetry over inland waters based on UAV and new autonomous micro-gauges - Jean-Christophe Poisson; Guillaume Valladeau; Nicolas Picot; François Boy (CNES, 2022)
The first radar altimetry missions were dedicated to the open ocean. However, continental water surfaces (enclosed seas, lakes, rivers, flooding areas...) can also be measured by satellite altimetry. For many years now, satellite altimetry is increasingly used to monitor inland waters all over the globe, and even more with the advent of delay doppler radar altimeter embedded on the Copernicus Sentinel-3 and Sentinel6-MF missions, and the future SWOT mission based on interferometric radar imagery. For these instruments, new algorithms are currently being developed to support improved data processing over hydrological surfaces in order to achieve significant accuracy improvements. There is therefore an increasing need for new in-situ systems to provide reference data for large-scale Calibration/Validation (Cal/Val) activities over inland water.
In this context, vorteX.io designed a lightweight remote sensing instrument, inherited from the specifications of radar altimeters on board altimetric satellites, capable of providing water height measurements with centimeter-level accuracy and at high frequency. Mounted on a flying drone, the system combines a LiDAR system and a camera in a single payload to provide centimetre-level water surface height measurements, orthophotos, water surface mask and water surface velocity throughout the drone flight. The vorteX.io system is the result of a review of existing in-situ systems used for Cal/Val of satellite altimetry in hydrology or operational monitoring of water heights (often to anticipate potential river floods or to monitor reservoir volumes). As the lightweight altimeter is inspired from satellite altimetry, water level measurements are directly comparable to satellite altimeter data. Thanks to the UAV capability, water measurements can be performed on long distances along rivers, and at the same location and time as the satellite pass. New hydrological variables are planned to be added in the next future (water surface temperature, river discharge, turbidity, …).
The drone-embedded lightweight altimeter has been successfully used during several measurement campaigns for the French space agency (CNES) as part of the Cal/Val of Sentinel-3A, Sentinel-3B, and Sentinel-6 missions. This innovative instrument is being considered as one of the means of the in-situ validation of the future SWOT mission for hydrology. We present here the results of the measurements performed by the vorteX.io VTX-1 altimeter in different hydrological contexts in France in 2020 and 2022.
In addition, vorteX.io offers an innovative and intelligent service for monitoring hydrological surfaces, using easy-to-install and fixed remote sensing in-situ instruments, based on compact light-weight altimeter also inspired from satellite technology: the micro-stations. Micro-Stations directly address the needs of in-situ measurements (Fiducial Reference Measurements) for Cal/Val activities over inland water bodies. Indeed, the vorteX.io micro-station is able to automatically wake up and perform measurements at the exact moment of the satellite overflight thanks to satellite ephemerides. With this feature, there is no time delay between in-situ measurements and the satellite overflight. Water heights are provided with respect to the ellipsoid or local geoid. All geophysical corrections required can be applied on the fly. Different hydrological variables are measured (water surface height, the associated uncertainty, water surface speed) and new others are planned to be added in the next future (water surface temperature, turbidity, …). The vorteX.io solution has already been used in various CNES and ESA projects and will be implemented in the ESA St3TART project and will be used for Cal/Val activities of the future SWOT mission on the Garonne River.